Genome-Wide Identification, Classification and Expression Analyses of MADS-Box Genes Reveal Their Role in Stem Gall Formation and Expansion of Zizania latifolia - Zhang, Zhiping; Xiao, Meng; Song, Sixiao; Jiang, Yifeng; Zhu, Xinrui; Shi, Lingtong; Zheng, Xiaomeng; Jiang, Jiezeng; Miao, Minmin (Agronomy (Basel), 2023)
MADS-box genes are important transcription factors in eukaryotes that are involved in regulating the growth and development of many plants. Jiaobai is a special aquatic vegetable formed through the stem expansion of Zizania latifolia infected by Ustilago esculenta and is wildly cultivated in Southeast Asia. To date, the biological function of MADS-box genes in Z. latifolia remains largely unknown. In this study, a genome-wide search for MADS-box genes in Z. latifolia was performed, and 87 MADS-box genes were identified. According to the phylogenetic analysis, there were 27 type I genes and 60 type II genes. The type I genes were mainly distributed in the Mα, Mβ and Mγ subfamilies, and the type II genes were divided into 14 subfamilies and unevenly distributed across 17 chromosomes. The encoded protein sequences ranged from 91 to 433 amino acids, the number of exons was 1~14, and most type I genes did not contain introns. The promoter region contained a large number of functional domains related to light response, plant hormones, stress and the meristem. An analysis of the expression patterns showed that there were massive differences in the expression of the MADS-box genes in different tissues, with six genes highly expressed in leaves and eight genes highly expressed in the stem apical meristem. Photoperiod and temperature were found to regulate the formation of the stem gall (SG) of Z. latifolia, and short-day (SD) conditions had an obvious promoting effect. ZlMADS57 and ZlMADS85 were significantly increased in SG under SD. Further analysis of the expression levels of MADS-box genes during the developmental stages of Z. latifolia found that the ZlMADS45, ZlMADS57, ZlMADS81 and ZlMADS85 were highly expressed 10 days before the SG formation, and ZlMADS66 reached its highest value on the day when the SG began forming. ZlMADS14, ZlMADS15, ZlMADS32, ZlMADS36, ZlMADS59 and ZlMADS71 were highly expressed after SG expansion, indicating that the MADS-box gene may play an important role in regulating SG formation and the subsequent expansion of Jiaobai. This study provides a reference for the functional identification of the MADS-box gene family and establishes a foundation for regulating the maturity of Z. latifolia.